Preparation and identification of some transition metal complexes of new schiff base ligand derived from 4-aminoantipyrene - Hadi Kadhim, Salih; Noor Al –ShareefyAbbas; Abbas Jawad, Waleed (Al-Qadisiyah Journal of Pure Science, 2018)
The research includes preparation of a new complexes of some transition metal ions Fe(III) ,Co(II),Ni(II),Cu(II) with Schiff base obtained from condensation reaction of 4-aminoantipyrene with benzylideneacetophenone in an ethanolic solution to give the ligand : 4-( 1,3-diphenylallylidene)amino)-1,5-dimethyl 2-pholenyl-1-pyraz ol-3-one . The identity of these liganl have been characterized by Infrared (IR) and ultraviolet-visible (UV – visible) specta and determine C.H.N ,metals , elemental analysis and measurements of magnetic susceptibility , melting point and molar conductivity.The results showed that all the complexes have (1:2)(metal:ligand) molar ratio , with the exception to Ni(II) complexes which have (1:1)(metal:ligand) molar ratio, from the observations the geometric structure of the synthesized complexes were suggeste .